1, 3-Dipolar cycloaddition of 3-alkylsulfanyl-2-arylazo-3-(tert-cycloalkylamino)acrylonitriles with N-methyl- and N-phenylmaleimides. Issue 9 (4th March 2015) - Belskaya, Nataliya P.; Lesogorova, Svetlana G.; Subbotina, Julia O.; Koksharov, Aleksandr V.; Slepukhin, Pavel A.; Dehaen, Wim; Bakulev, Vasiliy A.
Abstract: A series of 1, 2-diaza-1, 3-butadienes with terminal S, N -acetal function were obtained and reacted with N -methyl- and N -phenylmaleimides. As a result of the 1, 3-dipolar cycloaddition, a range of new functionalized nonaromatic heterocyclic compounds including: octahydro-1 H -pyrrolo[3, 4- a ]indolizine, octahydropyrrolo[3′, 4′:3, 4]pyrrolo[1, 2- a ]azepine, hexahydropyrrolo[3′, 4′:3, 4]pyrrolo[2, 1- c ][1, 4]oxazine and -thiazine, were obtained with good yields in mild conditions. Experimental and theoretic results allowed establishment of a relationship between the structures of the tert -cycloalkylamine group and the activity of the azomethine ylides generated. Graphical abstract: